Answer:
a) P(A) = 0.33
b) P(B) = 0.56
c) P(AUB) = 0.78
d) P(A∩B) = 0.11
Step-by-step explanation:
Y=mx+b
Mx is the rate of change
B is your starting point
Started with 1000, A
-200 is the rate of change, D
Answer:
80
Step-by-step explanation:
7x +3 = 5x + 25
2x + 3 = 25
2x = 22
x = 11
Answer:
<h2>(4x + 3) + (-2x + 4) = 2x + 7</h2>
Step-by-step explanation:
(4x + 3) + (-2x + 4)
= 4x + 3 - 2x + 4 <em>combine like terms</em>
= (4x - 2x) + (3 + 4)
= 2x + 7
I don't know but I guess there is an answer